Breastfeeding practices after a counselling intervention for factory workers in Bangladesh. Issue 2 (26th November 2020) - Haider, Rukhsana; Thorley, Virginia; Yourkavitch, Jennifer
Abstract: Breastfeeding may be particularly challenging for female factory workers who have long working hours and inadequate access to health information and care. In Chattogram, Bangladesh, a peer counselling intervention was undertaken to improve infant feeding practices of factory workers. Counselling started during pregnancy and continued until children were 18 months old. This article presents the results of a cross‐sectional survey undertaken during 2 weeks in March–April 2017, after the project's conclusion. The aim was to compare breastfeeding practices, specifically early breastfeeding initiation and exclusive breastfeeding (EBF), among factory workers who had received peer counselling in the intervention areas (IA) with those of non‐counselled factory workers in the nearby comparison areas (CA). Six female interviewers, trained over 3 days, conducted interviews at the workers' homes. Data were analysed to assess the association of peer counselling with infant feeding practices. Factory workers ( N = 382) with infants between 0 and 18 months of age participated in the survey, in IA ( n = 188) and in CA ( n = 194). Although there were more health facility deliveries among the CA workers, only 43 (22%) of those workers had initiated breastfeeding within 1 h of birth versus 166 (88%) of the IA workers ( p < .001). EBF prevalence on 24‐h recall in infants aged 0–6 months was only 7/83 (8%) for the CA workers versus 73/75 (97%) for IA workers ( p < .001). The survey showed that breastfeeding practices of factory workers in the IA after the intervention were significantly better than those of factory workers in the CA.